Role of Motivation on Employees Job Satisfaction (A case study in Injibara Poly Technique College) - Kefale Dagnew (ASTU, 2016)
This research was carried out to investigate the role of motivation on employees‟ job satisfaction in Injibara Poly Technique College. The researcher has employed descriptive survey type of study design. To describe or explain the results of the respondents based on instruments employed the descriptive analysis tools; frequency, percentage distribution, mean and standard deviation were employed. The sampling procedure follows probabilistic sampling technique; the study has employed simple random sampling - lottery method. The total or Static population in Injibara Poly Technique College was 140 employees‟. In the research a sample containing 103 employees‟ were randomly selected according to Krejcie and Morgan (1970) published table among the static population of 140 employees‟ of Injibara Poly Technique College. This research is limited to the questionnaires drawn from the short form Minnesota Satisfaction Questionnaires (MSQ) on extrinsic and extrinsic motivation variables to assess its role on employees‟ job satisfaction. The researcher recommends future study may involve personality factors like skill level and work perception of employees‟ relation with motivation and job satisfaction.
Keywords: Intrinsic motivation, extrinsic motivation and employees „job satisfaction.